Circulating level of microRNA-126 may be a potential biomarker for recovery from smoking-related vascular damage in middle-aged habitual smokers. (1st June 2015) - Sugiura, Tomonori; Dohi, Yasuaki; Yamashita, Sumiyo; Iwaki, Soichiro; Ito, Shiori; Sanagawa, Akimasa; Ohte, Nobuyuki; Fujii, Satoshi
Abstract: Background: Cigarette smoking promotes vascular endothelial damage and accelerates progression of atherosclerosis. The purpose of this study was to examine whether the circulating level of vascular endothelium-enriched microRNA-126 (miR-126), which is highlighted as a regulator of gene expression, would serve as a novel biomarker for recovery from smoking-related vascular damage. Methods: Middle-aged male smokers ( n  = 30) were enrolled and instructed to stop smoking. Their clinical profiles and laboratory findings including expression of miR-126 were investigated before and after 8 weeks of smoking cessation. Serum levels of cotinine, metabolites of nicotine, were measured to confirm smoking cessation. Endothelial function for peripheral small vessels was assessed and expressed as reactive hyperemia peripheral arterial tonometry (RH-PAT) index. The expression of miR-126 in plasma was analyzed by quantitative real-time PCR. Results: At baseline, serum cotinine levels were inversely correlated with RH-PAT index ( r  = − 0.48, P  < 0.01) and positively correlated with levels of metabolic parameters such as non-HDL cholesterol ( r  = 0.53, P  < 0.01) and HOMA-IR ( r  = 0.52, P  < 0.01). The RH-PAT index was not significantly changed after 8 weeks in all subjects, because only 13 subjects could attain smoking cessation. However, changes in the RH-PAT index showed a significant correlation with those in systolic blood pressure ( r  = − 0.54, P  < 0.01). In smokers who completely attained smoking cessation ( n  = 13), RH-PAT index and plasma levels of miR-126 were significantly increased ( P  < 0.05, respectively). Conclusions: Endothelial damage was improved and plasma levels of circulating miR-126 were increased after 8 weeks of smoking cessation. These findings suggested a potential use of miR-126 as a biomarker for recovery from smoking-induced vascular damage. Highlights: Cigarette smoking promotes vascular endothelial damage. Middle-aged male smokers were enrolled and instructed to stop smoking. Their clinical profiles and circulating levels of miR-126 were investigated. Endothelial function and circulating miR-126 were recovered after 8 weeks. The circulating miR-126 may be a biomarker for smoking-related vascular damage.